Effect of Problem Based Learning on Student Learning Outcomes on Theme 2 Clean Air for Health Subtheme 1 the Body's Way of Processing Clean Air Class V SD Negeri 4 Suhutnihuta Pardomuan - Kevin Martin; Natalina Purba; Lisbet Novianti Sihombing (Indonesian Journal of Advanced Research, 2023)
The aim of this research is to determine whether or not there is an influence of the Problem Based Learning Model on Student Learning Outcomes in Theme 2 Clean Air for Health Sub-theme 1 How the Body Processes Clean Air Class V SD Negeri 4 Suhutnihuta Pardomuan Academic Year 2023/2024. The population in this study were all fifth grade students at SD Negeri 4 Suhutnihuta Pardomuan, Palipi District, Samosir Regency, Academic Year 2023/2024 in the Odd Semester. The sampling technique used in this research is total sampling so that the sample used in this research is all class V students, namely 30 people. This research design is a pre-experimental research design type One-Group Pretest-Posttest Design. Based on the results of the research and discussion that have been presented, it can be concluded that the results of research have been carried out by researchers on class V students of SD Negeri 4 Suhutnihuta Pardomuan. by carrying out One Group Pretest – Posttest there is an influence on student learning outcomes seen from the acquisition of learning outcomes with an average pretest score of 53.20 in the category of not reaching and not exceeding the KKM (70), while the average posttest score is 84.13 which is in the good category and the difference between the pretest and posttest averages is 30.93, which means there has been an increase after using the Problem Based Learning model which has an influence on student learning outcomes in Theme 2 Subtheme 1 How the Body Processes Clean Air Class V SD Negeri 4 Suhutnihuta Pardomuan.